Synthesis of NaYF4: Yb, Tm Nanoparticles by Solvothermal Method and Characterization by Upconversion Visible Radiation Fluorescence. (December 2018) - Rubén Mallqui, Ch; Puga, Rubén; Acosta, Dwight; Hernandez, José M.; Loro, Héctor
Abstract: We report the synthesis of NaYF4 nanoparticles doped with rare earth ions Yb 3+, Tm 3+, using the solvotermal method. These nanoparticles were synthesized varying the concentration of Tm 3+, considering 0.5%; 1.0%; 1.5% and 2.0% of Tm 3 + instead of the Y ions in NaYF4 in order to study variations in their emissions around 480 nm. The results show a better performance of 1% Tm 3+ doped nanoparticles. We report emission spectroscopy results using a 980 nm diode laser.